2020
DOI: 10.1111/iej.13310
|View full text |Cite
|
Sign up to set email alerts
|

Abstracts of published randomized controlled trials in Endodontics: reporting quality and spin

Abstract: AimsTo assess the reporting quality of recently published randomized controlled trial (RCT) abstracts in Endodontics, to investigate factors associated with reporting quality, and to evaluate the existence and characteristics of spin, that is using reporting strategies that distort study results and misguide readers.MethodologyThe PubMed database was searched to identify abstracts of RCTs in the field of Endodontics published during 2017 to 2018. Two authors assessed the reporting quality of each included abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 49 publications
9
36
1
Order By: Relevance
“…However, the existence of this structure does not seem to provide sufficient information. Our results are consistent with others (Fang et al, 2020;Bero et al,1998) which appears a need to use specific strategies to implement research-based recommendations to ensure a change in approach. Study concluded that journals' active implementation of the CONSORT -A guidelines is associated with improved completeness of reporting of RCTs (Speich et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the existence of this structure does not seem to provide sufficient information. Our results are consistent with others (Fang et al, 2020;Bero et al,1998) which appears a need to use specific strategies to implement research-based recommendations to ensure a change in approach. Study concluded that journals' active implementation of the CONSORT -A guidelines is associated with improved completeness of reporting of RCTs (Speich et al, 2020).…”
Section: Discussionsupporting
confidence: 91%
“…With the publication of CONSORT extension for abstract reporting (CONSORT-A), it was endorsed by the World Association of Medical Editors, the International Committee of Medical Journal Editors, and the Council of Science Editors (Chhapola et al, 2018). Studies have been conducted based on CONSORT-A to evaluate the quality of abstract reporting in different areas and certain specialties (Germini et al, 2019;Faggion & Giannakopoulos, 2012;Chow et al, 2018;Fang et al, 2020;Gallo et al, 2020). However, these studies indicated that the reporting quality of RCT abstracts are consistently suboptimal.…”
Section: Introductionmentioning
confidence: 99%
“…Using the CONSORT explanation and elaboration statement for abstracts of parallel group randomized trials by Moher et al [4] and previous reports [ 5 , 14 ], two reviewers worked independently (DGW and YGZ) to make a judgment on whether an item in the RCT abstract was adequately reported. These two reviewers were calibrated through rounds of 10 randomly selected abstracts until strong agreement (Cohen's κ statistic ≥0.90) was reached.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of spin was originally used in fields such as culture, politic and commerce, and is defined as a form of propaganda that could affect public views on an organization or public figure [5] . In health care, it was defined by Boutron and colleagues in 2010 as “specific reporting strategies from whatever motive, highlighting the interventions are beneficial despite the statistically non-significant differences for the primary outcomes” [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation